The role of bioimpedance status in the diagnosis of presarcopenia in elderly and elderly patients with type 2 diabetes mellitus - Ruslan N. Obyedkov; Evgeny I. Dedov; Irina G. Pshennikova (Consilium Medicum)
Background. Determination of skeletal muscle mass (SMM) for the diagnosis of sarcopenia using bioimpedance analysis of body composition (BIAST) is a well-recognised method. However, as data are accumulating, alternative possibilities for its diagnosis are occurring, particularly the determination of phase angle (PA) and other BIAST parameters.